(untitled) (Scientific journal of the Fergana State University, 2023)
This article is intended to highlight the technologies of preparing future teachers for tutoring based on modern approaches. It touches upon the content and essence of the diagnostic, motivational, implementation and analytical stages of the tutor activity. The effectiveness of the use of such technologies in tutoring activities as individual tutor counseling, group tutor counseling, tutor (educational tutor seminar), training, educational activities is also highlighted.